Sub-clinical orthostatic hypotension is associated with greater subjective memory impairment in older adults - Kenny, Rose; Mc Crory, Cathal (My University, 2017)
Introduction: Orthostatic blood pressure (BP) is a measure of cardiovascular autonomic function. Orthostatic BP dysregulation may lie on the causal pathway to dementia. Subjective memory impairment (SMI) is commonly reported by older people some of whom may progress to dementia. We hypothesised that sub-clinical orthostatic hypotension would be associated with SMI and explored these associations according to sex. Methods: Cross-sectional analysis of data from 4340 participants aged 50 and over collected during the first wave (2009–2011) of the cohort study, The Irish Longitudinal Study on Ageing. Subjective memory was rated according to a 5-point scale ranging from ‘poor’ to ‘excellent’. BP was measured during orthostatic stress using continuous non-invasive beat-to-beat recording over 2 min. Results: 2% reported ‘poor’ subjective memory, 12.3% ‘fair’ , 38% ‘good’, 33% ‘very good’ and 14.6% ‘excellent’. After controlling for several potential confounding factors including cardiovascular risk, objective cognition, and depressive symptoms mean systolic orthostatic BP was lowest in those with poor subjective memory: 92.2 mmHg (CI95% = 87.1, 97.3) versus excellent 99.3 mmHg (CI95% = 97.4, 101.2); p = 0.011. Further adjustment for supine systolic BP suggested that men with poor subjective memory reached the lowest average systolic orthostatic BP and had the greatest impairment in systolic orthostatic BP stabilisation to baseline levels at 10 s post-stand ( 6.64 mmHg; CI95% = 11.49, 1.79; p = 0.007). Conclusions: Sub-clinical orthostatic hypotension is associated with SMI, and there are sex-specific relationships evident in this population-based cohort. Subtle cardiovascular autonomic dysfunction may represent a modifiable risk marker at an early stage of cognitive decline in older adults.
PUBLISHED
Keywords: orthostatic hypotension, subjective memory, autonomic function; Ageing